Firm Performance and Trade with Low-Income Countries: Evidence from China - Hans-Jörg Schmerer; Luhang Wang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Krugman's (1979, 1980) monoplistic competition model of trade showed that countries with more similar per-capita GDP trade more with each other. Does this mean that developing countries shift trade towards developed countries as a result of high economic growth? The results reported in this paper challenge the link between per-capita GDP and trade predicted by the force of gravity. The matched customs-manufacturing firm data used in this study reveal a rising low-income country trade share around and after China's accession to the World Trade Organization. Based on this stylized fact we analyze the link between firm performance and different export strategies. We find strong evidence for sequential sorting into different export-modes. i) only the most productive firms export to low-income countries, ii) export to low-income countries is coupled to export to high-income countries, iii) younger firms solely export to export markets with higher potential, and iv) low-income markets are served additionally by older firms. Moreover, we find that entry into simultaneous exports to low- and high-income destinations is associated with a higher productivity compared to the average productivity measured by incumbents' firm performance.
Keywords: F10; O11; F15; 330